Proceedings of the 11th ACM Symposium on Document Engineering 2011
DOI: 10.1145/2034691.2034748
|View full text |Cite
|
Sign up to set email alerts
|

Making accessible PDF documents

Abstract: Accessibility features in the Adobe Portable Document Format (PDF) help facilitate access to electronic information for people with disabilities. This workshop explores how to create accessible PDF documents, from within Adobe Acrobat and other applications; how to use the Adobe Acrobat PDF accessibility checker and repair workflow; best practices for accessibility; and how accessibility has been built into forthcoming ISO standards (PDF/UA, PDF 32000-2).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 1 publication
0
6
0
Order By: Relevance
“…Of those with severe symptoms, 64% reported an intention to reduce working hours, 47% intended to leave the workforce and 44% intended to leave their employing organisation. The organisation reported that it has a majority female workforce of 81.9%, slightly higher than the UK average (Devine & Foley, 2020) with 40.6% aged between 41 and 55 years suggesting 33% working through perimenopause and menopause.…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…Of those with severe symptoms, 64% reported an intention to reduce working hours, 47% intended to leave the workforce and 44% intended to leave their employing organisation. The organisation reported that it has a majority female workforce of 81.9%, slightly higher than the UK average (Devine & Foley, 2020) with 40.6% aged between 41 and 55 years suggesting 33% working through perimenopause and menopause.…”
Section: Resultsmentioning
confidence: 96%
“…Menopause needs to be treated differently, firstly, menopause as an issue for a growing older workforce working longer and secondly menopause is an issue that includes everyone needs to know about. This organisation employed a majority female workforce of 81.9%, higher than the national average with 78% in healthcare settings followed by 70% in education (Devine & Foley, 2020). A third of this organisation's workforce (40.6%) are aged between 41 and 55 years and working through perimenopause and menopause.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While the importance of tagged PDFs in accessibility has led to studies on generating tagged PDFs (Moore, 2009), other authors have focused on how to create accessible PDFs (Devine, Gonzalez, & Hardy, 2011) from Adobe and other applications. Flexible software architectures that automatically generate accessible PDF documents from tools such as Adobe InDesign and Microsoft Word have also been proposed (Darvishy et al, 2010;Darvishy et al, 2011).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Women make up the largest proportion of the international health workforce, with the largest representation in the nursing profession (Boniol et al, 2019). Noticeably women in the workforce adopt more roles in the caring professions (nursing, teaching and care work) with 79% of UK jobs in health and social care held by women (Devine & Foley, 2020); and in nursing the Royal College of Nursing (2020b) report 89.3% female registered nurses as opposed to 10.7% of men.…”
Section: Introductionmentioning
confidence: 99%